Short and long-term effects of nanobiomaterials in fish cell lines. Applicability of RTgill-W1. (December 2022) - Hernández-Moreno, D.; Navas, J.M.; Fernández-Cruz, M.L.
Abstract: Nanobiomaterials (NBMs) are nanostructured materials for biomedical applications that can reach aquatic organisms. The short and long-term effects of these emerging contaminants are unknown in fish. The RTgill-W1 cell line has been proposed as a model to predict the acute toxicity of chemicals to fish (OECD Test Guideline nº 249). We assessed the applicability of this cell line to study the short and long-term toxicity of 15 NBMs based on hydroxyapatites (HA), lipid (LSNP/LNP), gold, iron oxide, carbon, poly l -Lactide acid (PLLA) fibers with Ag and poly (lactide-co-glycolide) acid. Two more rainbow trout cell lines (RTL-W1, from liver, and RTS-11, from spleen) were exposed, to identify possible sensitivity differences among cells. Exposures to a range of concentrations (0.78–100 μg/mL) lasted for 24 h. Additionally, the RTgill-W1 was used to perform long-term (28 d exposure) and recovery (14 d exposure/14 d recovery) assays. Cells were exposed to the 24 h-IC20 and/or to 100 μg/mL. A triple cytotoxicity assay was conducted. After 24 h, only PLLA Fibers-Ag showed cytotoxicity (IC50 < 100 μg/mL). However, the NBMs in general provoked concentration-dependent effects after long-term exposures, except the LSNPs. A recovery of viability was only observed for AuNPs, AuNRods, Fe3 O4 PEG-PLGA, MgHA-Collag_Scaffolds, Ti-HA and TiHA-Alg NPs.These results evidenced the need to test the long-term toxicity of NBMs and showed differences in cytotoxicity probably associated to different mechanisms of toxic action. The RTgill-W1 was useful to screen short and long-term toxicities of NBMs and appears as a promiseful model to assess possible toxicity of NBMs in fish. Graphical abstract: Image 1 Highlights: The RTgill-W1 is useful to screen short- & long-term toxicities of nanobiomaterials. NBMs are not acutely toxic but induced long-term effects. Depending on the NBM tested, different patterns of recovery were observed. Results indicated different mechanisms of toxic action for the fifteen NBMs.